Corruption Offenses Concerning Civil Servants with Special Status within the Ministry of Internal Affairs - Ionescu Dumitrache, Ana Alina; Salcianu, Nela (Acta Universitatis Danubius. Juridica, 2024)
In this paper, we aim at highlighting some aspects related to corruption offenses provided for by the Criminal Code and Law no. 78/2000 for the discovery, prevention and sanctioning of acts of corruption, committed by civil servants with special status within the Ministry of Internal Affairs (MAI). At the same time, this study emphasizes a special concern for the prevention and combating these offenses by identifying the risks and vulnerabilities existing within the Romanian Police that can influence the correct functioning of this structure. Corruption among public servants with special status within the MAI erodes moral values, mainly integrity, a trait that requires them to exercise their duties according to certain values and principles, without compromise. We believe that an important role in reducing corruption among police officers and in preventing these acts can also be played by harshening the penalties, although, currently, there is an aggravated version of the sanctioning of acts of corruption committed by police officers, provided for in art. 7 of Law no. 78/2000, a variant that consists in sanctioning with the penalty provided for in art. 289 and 291 Criminal Code, whose limits are increased by one third. The main methods employed were survey, observation and case study. Therefore, at the end of our study, de lege ferenda proposal: as, in the case of the crime of assault (art. 257 of the Criminal Code) there is a paragraph in which the sanction is provided with the penalty provided by law whose limits are increased by half if the crime is committed against a policeman in the exercise of his duties, the punishment applied based on the special quality of the victim, a policeman, the same should be done in the case of the crime of bribery (art. 289 of the Criminal Code) respectively, the addition of a new paragraph stipulating that if the acts were committed by a police officer in the exercise of his duties, he shall be punished with the punishment provided by law for that crime, the limits of which should increase by half. Our belief is that these legislative amendments are necessary to lessen the incidence of corruption among police officers, thereby making them aware of the risks associated with bribery from the standpoint of the more severe punishment system.